Dissipation kinetics and risk assessment of chlorantraniliprole and lambda-cyhalothrin in okra (Abelmoschus esculentus L.) and soil - KHOKHAR, CHETNA; AHLAWAT, SUSHIL; CHAUHAN, REENA; YADAV, SURENDER SINGH; KUMARI, NISHA (The Indian Journal of Agricultural Sciences, 2026)
A field investigation was conducted in April 2023 to elucidate the dissipation kinetics, persistence and risk assessment of chlorantraniliprole and lambda-cyhalothrin applied as ready-mix insecticide in okra (Abelmoschus esculentus L.) and associated soil. Okra fruits and corresponding soil samples were collected after pesticide application at the recommended dose (28 g a.i./ha) as well as at higher dose rates i.e. 35 g a.i./ ha (1.25SD) and 56 g a.i./ ha (DD). The samples were analysed using a validated QuEChERS extraction protocol followed by GC-MS/MS quantification. Both insecticides confirmed to first-order dissipation kinetics, with half-lives of 1.40–4.36 days in okra fruits. Residues decline below the MRL within 6 days after application, establishing safe pre-harvest intervals. Dietary and soil risk assessments, based on estimated daily intake (EDI) and risk quotient (RQ), indicated negligible human and ecological risk. These findings provide critical data for residue management, regulatory compliance and suitability of chlorantraniliprole and lambda-cyhalothrin in okra cultivation.